Cadmium isotope systematics for source apportionment in an urban–rural region. (February 2022) - Liao, Rong; Ratié, Gildas; Shi, Zeming; Šípková, Adéla; Vaňková, Zuzana; Chrastný, Vladislav; Zhang, Junji; Komárek, Michael
Abstract: Cadmium (Cd) is a highly carcinogenic metal that can cause toxic reactions, even at low concentrations. In the urban–rural region of Chengdu (China), the Cd concentration of soil ranged from 0.02 mg kg −1 to 5.03 mg kg −1 . To decipher Cd source apportionment, samples were collected from topsoil, weathered material, and bedrocks (profiles reaching 200 m in depth) and from local anthropogenic endmembers (pigment, fertilizer, and urban dust). Geogenic Cd weathering processes were determined using the alteration index and exchangeable fraction of Cd in soil. Simultaneously, the Cd isotope composition was measured to determine the geogenic isotopic trend of Cd during weathering and the impacts of anthropogenic inputs on the soil surface. Overall, we observed a high variability in the mass transfer of Cd, indicating the presence of multiple Cd sources. Chemical weathering led to the preferential depletion of heavy Cd isotopes through mineral dissolution and the preferential enrichment of light Cd isotopes during Cd sorption onto newly formed soil phases (−0.35‰ < Δ 114/110 Cdsoil-bedrock < 0.01‰). Anthropogenic inputs were associated with a wide range of δ 114/110 Cd values (−0.50 ± 0.02‰ to 0.08 ± 0.02‰). It can be inferred that anthropogenic inputs alter the typical Rayleigh fractionation observed during chemical weathering and modify the Cd isotopic trend in the soil surface of urban–agricultural areas. Graphical abstract: Image 1 Highlights: Chemical weathering led to a preferential depletion of heavy Cd isotopes. Soil chemical parameters influenced the enrichment of light Cd isotopes in soil. Land use and history controlled the influence of anthropogenic inputs vs weathering. Most soil profiles highlighted the influence of anthropogenic inputs of Cd.